The Effect Of Physical Activity And Motor Skills On Social Interaction In Children Aged 3-5 Years - Vinky Valensia; Anggri Dwi Nata; Rahmat Sanusi (Journal Physical Health Recreation (JPHR), 2025)
This study aims to determine the influence of physical activity and motor skills on social interaction in children aged 3-5 years. This research can address the issues faced by early childhood children who lack social interaction with their peers and serve as input in program planning related to the problems that occur, namely motor skills and social interaction in early childhood, as well as broaden the understanding, especially regarding physical activity and motor skills on social interaction in early childhood. The type of research is quantitative research using the Pre-Experimental method. The population in this study consists of 30 people and the sample consists of 15 people. The data collection technique used is in the form of questionnaires or survey sheets. The data analysis technique uses a Likert scale as the scoring scale and the average value for the validation criteria using the presentation of the assessment scores. The results of this study were conducted using a One-Group Pretest-Posttest, which includes a pretest to determine the initial condition, followed by a post-test to determine whether there is an effect of physical activity and motor skills on social interaction in children aged 3-5 years after treatment. There is a significant influence between the impact of physical activity on social interaction in children aged 3-5 years and the influence of motor skills on social interaction in children. The result of the T-test for motor skills is 15.62, greater than the result of the T-test for physical activity, which is 1.5.